Uncertainty quantification in natural frequencies and radiated acoustic power of composite plates: Analytical and experimental investigation. (January 2015) - Sepahvand, K.; Scheffler, M.; Marburg, S.
Highlights: Uncertainty in material and vibroacoustic properties of composites is investigated. Uncertain quantities are represented by the generalized polynomial chaos expansion. The distribution type of uncertain parameters is identified from experimental data. Non-intrusive stochastic method is used to calculate the unknown output expansions. The method accuracy and impact of uncertainty on frequency and ERP are presented. Abstract: In this study, the impact of elastic parameter uncertainty on the natural frequency and the radiated acoustic power of laminated composite plates is investigated. Due to structure complexity, composites exhibit great variability in mechanical properties. We adopt a model to develop stochastic natural frequencies and the equivalent radiated power of rectangular laminated plates where elastic parameters, natural frequencies and acoustic power density are represented using generalized polynomial chaos expansions with arbitrary random basis. Available experimental data are used to realize the distribution type of the parameters by utilizing the Pearson model. This realization is then employed to identify orthogonal random basis for each uncertain parameter. A non-intrusive collocation based method is conducted in order to calculate the deterministic polynomial chaos coefficients of the natural frequencies and the acoustic power density. Numerical results show that the natural frequencies and as well as the radiated acoustic powers are strongly affected from uncertainty in input parameters.